TINJAUAN SOSIO KRIMINOLOGIS TENTANG EKSPLOITASI ANAK YANG DIPEKERJAKAN SEBAGAI BADUT MAMPANG DI KOTA BAUBAU - La Ode Ali Mustafa; Samaluddin Samaluddin; Yhoga Tama Maulana Dani (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
In writing this thesis, the author discusses the exploitation of children in the form of economic exploitation who are employed as mampang clowns. The purpose of writing this thesis is to find out what are the factors that cause the exploitation of children who work as mampang clowns in Baubau City. In addition, to find out how the efforts made by the Baubau City government in handling the exploitation of children who work as mampang clowns. This research is a qualitative legal paper where secondary data in the form of theory, definition and substance from various literatures and laws and regulations as well as primary data obtained from interviews, observations and field studies will then be analyzed with laws and the opinions of relevant experts. so that a clear and complete picture is obtained in order to produce a conclusion that can be used to answer the problem formulation. In addition, the efforts made by the government, especially the Office of Women's Empowerment and Child Protection in Baubau City in handling the exploitation of children who work as clowns, are preventive efforts, namely preventive measures by conducting socialization, repressive efforts, namely by conducting joint raids with the Social Service and City SATPOL PP. Baubau, and rehabilitation efforts, namely by providing guidance to children who have been caught in raids.